PERBANDINGAN RETURN AND RISK ANTARA SAHAM-SAHAM SYARIAH DAN NON SYARIAH YANG TERCATAT DI BURSA EFEK INDONESIA - Yuliani, Zakia (Manajemen Bisnis, 2015)
The research was conducted on the basis of a range of common problems in capital markets activities in Indonesia, the increasing development of alternative investment and to invest, investors should be better at determining the investment option. It is taken into consideration is the investor return and risk. In principle, investors expect high returns with minimal risk. Establishment LQ 45 is a superior collection of 45 stocks to facilitate investors in choosing. Public interest in increasing sharia-based economy, then formed the Jakarta Islamic Index (JII) to respond to the needs of information that meets the requirements of Shariah. It made an interesting study of comparison between stock returns and risk and non-Islamic sharia. Researchers use this type of survey research in the analysis. Using purposive sampling, researchers select stocks during the period of observation is always good listings on LQ 45 and JII. Each sample wascalculated return and risk to findout which one gives the stock return and risk greater.